USING MONTE CARLO SIMULATIONS TO ACHIEVE THE BEST RESPONSE FROM NITROGEN ON GRAZED PASTURE UNDER A LEGISLATED NITROGEN CAP IN NEW ZEALAND: A REVIEW - Grafton M; Bishop PA; Bretherton MR (Massey University)
Pastoral and crop farming systems have traditionally used the application of nitrogen (N) to achieve an optimal economic production response. This nitrogen response is estimated from an exponential function that approaches an as ymptote, which is typical of most fertilizer response curves. The optimal economic N response is often achieved when appli cation rates are greater than plant utilization rates, often resulting in leaching, nitrogen run-off, and volatilization of ni trogenous compounds. These losses can have an impact on freshwater quality and contribute to greenhouse gas (GHG) emissions. In New Zealand, urine from N-fertilized pasture grazed by dairy cattle has been shown to be the most problematic source of N losses. As part of New Zealand’s National Environmental Standards (NES), a synthetic N cap of 190 kgN ha-1yr-1 on grazed pasture and crops has been implemented to reduce nutrient enrichment of fresh water. This study reviewed the use of multiple split applications of N to improve N fertilizer use efficiency and pasture response and used Monte Carlo simulations to demonstrate improved response to split N applications rather than a single optimal application based on economic response. In addition, spreading accuracy also became less important as all the low-application variation occurred along the steepest part of the response curve where this variation results in added yield.
(c) The Author/s
Keywords: Dairy cattle, Fertilizer cap, Monte Carlo simulations, Nitrogen use efficiency, Nutrient management.